Challenges in Regulating Private Primary Health Care in Malaysia: Perceptions from Key Informants - Nur Azmiah Zainuddin; Kamaliah Mohd Noh; Zalilah Abdullah; Nur Hidayati Abdul Halim; Rima Marhayu Abdul Rashid; Ainul Nadziha Mohd. Hanafiah; Nor Idawaty Ibrahim; Safiee Ismail (Asian Journal of Medicine & Health Sciences, 2022)
Introduction: Malaysians can access primary health care services from public or private facilities. The Ministry of Health regulates the public services, and to a lesser degree, the private practices via the Private Healthcare Facilities and Services Act 1998. With the mushrooming of private medical clinics, issues of accessibility, inequity, and quality of care arise. Currently, there is limited data on the assessment of regulatory performance and this study aims to assess the challenges in regulating private primary health care to assist policy makers in addressing problems associated with private primary healthcare provision. Methods: A total of 23 key informants categorised into the regulator (7), provider (6), academia (5), media (2), and consumer (3), were interviewed. They were purposively selected through recommendation by research team members, participants or information searching from websites. All transcribed interviews were analysed in accordance with the principles of qualitative thematic analysis, using the manual method in identification and analysing the themes. Results and Discussion: There were five major themes explaining the challenges in regulating private primary health care pertaining to the regulator, regulations, provider, facility, and the market. Among the main challenges were uncoordinated and fragmented enforcement by multiple regulatory bodies, poor enforcement of the private sector due to resources constraint of the main regulatory authority, and gaps in the regulations for provider competencies, facility monitoring and third-party administrator regulation. The main recommendations to improve the regulation of the private sector included alignment of the policy environment to foster coordinated enforcement for efficiency, strengthening of the main regulatory body, addressing the gaps in the regulations for congruency with the current health landscape in the country, data sharing for policy formulation, and to consider economic aspect of the regulations within the health market. Conclusion: Regulations for setting standards in providing primary health care in Malaysia have been fulfilled to some extent, however revision of the current regulations and the enforcement mechanism, involving relevant stakeholders, is timely, to achieve equitable and sustainable primary healthcare system.